Altitude training in team-sport athletes - Brocherie, F.; Girard, O.; Millet, G. (Hypoxia conditioning in health, exercise and sport: Principles, mechanisms and applications, 2025)
Team-sports performance requires complex technical and motor skills, tactical proficiency, and high developed specific physical capacities that encompass speed, agility, muscular strength, power, and endurance. Although outcomes in team sports hinge on technical and tactical actions, coaches and conditioning staffs are striving for innovative apporaches to improve players' physical performance. Therefore, several altitude/hypoxic methods, developed over time (see Chapter 4), could offer benefits to team-sport specific physical capacities and their underlying physiological mechanisms.